The unconscious and the transcendental: Husserlian phenomenology in intersubjective systems theory - Uljée, Rozemund (Frontiers in Psychology, 2023)
The relational turn in psychoanalysis can be identified by the replacement of Freudian drives for intersubjectivity as main regulative principle. “Intersubjective systems theory” is the name of one strand within the relational turn that explicitly locates its philosophical foundations in a number of phenomenological insights. In this paper, I investigate some of the essential phenomenological assumptions underlying intersubjective systems theory. I identify 2 main problems: 1. intersubjective systems theory relies on the premise that meaning is intersubjectively constituted, yet fails to offer an account of this constitution; 2. intersubjective systems theory is based on an ambiguous conception of the unconscious. The aim of this paper is to show how Husserlian phenomenology offers a valuable theoretical foundation for intersubjective systems theory in the sense that it presents a convincing account of the intersubjective constitution of meaning that in its very constitution allows for a dynamic and situational relation between consciousness and unconsciousness.